Blood Pressure Analysis Based on Nutritional Status and Lifestyle in Employees with Hypertension - Yessy Kurniati; Aminuddin Syam; Wahiduddin Wahiduddin; Zaenal Zaenal; Ahmad Arif Hidayat (Preventia : The Indonesian Journal of Public Health, 2024)
The incidence of hypertension continues to increase. Hypertension is related to lifestyle and nutritional status. This study aimed to analyze blood pressure based on the nutritional status and lifestyle of employees with hypertension. An analytic study with a cross-sectional design was conducted from July to September 2022 by recruiting all Hasanuddin University rectorate employees with hypertension. The total number of respondents in this study was 63 people. Data was collected by measuring blood pressure and anthropometry, while lifestyle risk factors were collected using a questionnaire. Pearson correlation was performed to measure the correlation between blood pressure and nutritional status. A t-test and ANOVA were used to measure differences in blood pressure based on lifestyle. This study found a correlation between Body Mass Index and systolic and diastolic blood pressure, and there was no difference in blood pressure, both systole and diastolic, based on smoking behavior, coffee consumption, stress levels, and physical activity patterns in employees with hypertension. Based on these results, it is recommended that people with hypertension improve their nutritional status and lifestyle.